The first GHEP-ISFG collaborative exercise on forensic applications of massively parallel sequencing. (November 2020) - Barrio, Pedro A.; García, Óscar; Phillips, Christopher; Prieto, Lourdes; Gusmão, Leonor; Fernández, Coro; Casals, Ferran; Freitas, Jorge M.; González-Albo, María del Carmen; Martín, Pablo; Mosquera, Ana; Navarro-Vera, Isabel; et al.
Highlights: Laboratories from 3 countries participated in the first GHEP-ISFG collaborative exercise on MPS. Six out of seven participating laboratories performed MPS analysis of auSTR. There was a high concordance among the results of the participating laboratories. All laboratories have a high degree of implementation of MPS technology. Abstract: One of the main goals of the Spanish and Portuguese-Speaking Working Group of the International Society for Forensic Genetics (GHEP-ISFG) is to promote and contribute to the development and dissemination of scientific knowledge in the field of forensic genetics. The GHEP-ISFG supports several Working Commissions which develop different scientific activities. One of them, the Working Commission on "Massively Parallel Sequencing (MPS): Forensic Applications", organized its first collaborative exercise on forensic applications of MPS technology in 2019. The aim of this exercise was to assess the concordance between the MPS results and those obtained with conventional technologies (capillary electrophoresis and Sanger sequencing), as well as to compare the results obtained within the different MPS platforms and/or the different kits/panels and analysis software packages (commercial and open-access) available on the market. The seven participating laboratories analyzed some samples of the annual GHEP-ISFG proficiency test (EIADN No. 27 (2019)), using Ion Torrent™ or MiSeq FGx® platforms. Six of them sent autosomal STR sequence data, five laboratories performed MPS analysis of individual identification SNPs, four laboratories reported MPS data of Y-chromosomal STRs, and X-chromosomal STRs, three laboratories performed MPS analysis of ancestry informative SNPs and phenotype informative SNPs, two labs performed MPS analysis of the mitochondrial DNA control region, and only one lab produced MPS data of lineage informative SNPs. Autosomal STR sequencing results were highly concordant to the consensus obtained by capillary electrophoresis in the EIADN No. 27 (2019) exercise. Furthermore, in general, a high level of concordance was observed between the results of the participating laboratories, regardless of the platform used. The main discordances were due to errors during the analysis process or from sequence data obtained with low depth of coverage. In this paper we highlight some issues that still arise, such as standardization of the nomenclature for STRs analyzed by sequencing with MPS, the universal uptake of a nomenclature framework by the analysis software, and well established validation and accreditation of the new MPS platforms for use in routine forensic case-work.